2020
DOI: 10.1007/s40037-020-00587-z
|View full text |Cite
|
Sign up to set email alerts
|

A mobile app to capture EPA assessment data: Utilizing the consolidated framework for implementation research to identify enablers and barriers to engagement

Abstract: Introduction Mobile apps that utilize the framework of entrustable professional activities (EPAs) to capture and deliver feedback are being implemented. If EPA apps are to be successfully incorporated into programmatic assessment, a better understanding of how they are experienced by the end-users will be necessary. The authors conducted a qualitative study using the Consolidated Framework for Implementation Research (CFIR) to identify enablers and barriers to engagement with an EPA app. Methods Structured int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 57 publications
1
17
0
2
Order By: Relevance
“…We found that some clinical teachers just rated performed or observed performance, indicating difficulties in understanding the prospective nature. Young et al reported similar findings (Young et al 2020). However, raters did not appear to experience these problems in the studies from Wijnen-Meijer et al (2013) and Cutrer et al (2020) where the retrospective and prospective rating scales were provided concurrently.…”
Section: The Nature Of Prospective Judgementsupporting
confidence: 54%
“…We found that some clinical teachers just rated performed or observed performance, indicating difficulties in understanding the prospective nature. Young et al reported similar findings (Young et al 2020). However, raters did not appear to experience these problems in the studies from Wijnen-Meijer et al (2013) and Cutrer et al (2020) where the retrospective and prospective rating scales were provided concurrently.…”
Section: The Nature Of Prospective Judgementsupporting
confidence: 54%
“…The comprehensive assessment of resident qualifications was highly valued by the directors, as it may offer more immediate and precise input and resolve weaknesses in the present system [ 23–25 ]. Both faculty and residents expressed favorable perspectives towards EPAs, viewing them as useful tools for providing feedback promptly following the observed patient encounter [ 19 , 26 ]. EPAs could enhance the professional capacities of participants.…”
Section: Resultsmentioning
confidence: 99%
“…Our students did not find the narrative feedback to be helpful in their learning, and this coincided with a large proportion of cards (41%) lacking coaching comments identifying specific, detailed or actionable areas for improvement. In a recent study, Young et al [21] observed that when faculty directly submitted comments using a mobile app to capture data on entrustable professional activities, feedback was received in a timely and frequent manner, and residents appreciated receiving the feedback within minutes of the encounter. It is possible that the change from preceptor-led comments with paper-based cards to student-led summarization of preceptor comments with the eClinic Card may have influenced timely submissions, extent, and quality of the written feedback.…”
Section: Critical Reflectionmentioning
confidence: 99%